Teaching Bahasa Indonesia in Vietnam in Indonesia-Vietnam Collaboration Prospect - Thanh, Ho Thi (Universitas Muria Kudus, 2023)
Indonesia adalah negara besar di Asia Tenggara. Namun di Vietnam, pemahaman masyarakat secara umum terhadap negara ini masih terbatas. Dalam konteks Komunitas ASEAN telah terbentuk, kebutuhan akan pemahaman dan kerjasama antar negara yang tergabung dalam Komunitas tersebut, termasuk Indonesia - Vietnam, semakin meningkat. Selain itu, dalam beberapa tahun terakhir, perkembangan kerjasama investasi antara Vietnam dan Indonesia turut mendorong peningkatan kebutuhan akan sumber daya manusia yang mampu berbahasa Indonesia dan mengetahui tentang Indonesia di Vietnam. Merespon kebutuhan tersebut, sejumlah lembaga pelatihan pendidikan di Vietnam Utara telah membentuk program pengajaran bahasa dan pengetahuan tentang Indonesia. Indonesia is a large country in Southeast Asia. However, in Vietnam, general public understanding of this country is still limited. In the context that the ASEAN organization has been formed, the need for understanding and cooperation between countries that are members of the Community, including Indonesia-Vietnam, is increasing. Apart from that, in recent years, the development of investment cooperation between Indonesia and Vietnam has also encouraged an increase in the need for human resources who are able to speak Indonesian and know about Indonesia in Vietnam. Responding to this need, a number of educational training institutions in North Vietnam have established language and knowledge teaching programs about Indonesia. This research aims to evaluate the development of Indonesia-Vietnam relations (especially economic relations) and the situation of teaching Indonesian and other knowledge about Indonesia in Vietnam in general and in North Vietnam in particular (mainly studying the teaching situation at the University of Social Sciences and Humanities, National University Vietnam, Hanoi). Apart from that, this research also discusses opportunities and challenges in teaching Indonesian, as well as their relationship to the prospects for cooperation between Indonesia and Vietnam